Process Simulation and Optimization of Anaerobic Co-Digestion - Inayat, Abrar; Ahmed, Shams Forruque; Djavanroodi, F.; Al-Ali, Fatima; Alsallani, Mira; Mangoosh, Shama (Frontiers in Energy Research, 2021)
Anaerobic digestion (AD) is an established method that has been extensively utilized for waste management, waste treatment, and biogas production. Anaerobic co-digestion (AcoD) is regarded as a practical approach to address substrate characteristics and system optimization issues. The distinction between AcoD and mono-digestion is that AcoD has a higher organic loading and significant substrate composition variation. There are many factors involved in AcoD which affect the biogas plant's production ability and performance. This article gives an overview of the various operating factors involved in AcoD, simulation of AcoD process and optimization of the overall process via response surface methodology (RSM) approach to predict the optimum conditions for maximum biogas yield. This review discusses a framework for designing, developing, and optimizing biogas production systems that incorporate various factors. Temperature, co-substrate concentration, inoculum ratio (%), and C/N ratio are the most critical parameters for AcoD optimization.